2013
DOI: 10.1021/om400339t
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Thia-Fries Rearrangements of Electron-Rich Ferrocenes and the Unanticipated Formation of Diferrocenyl Sulfate from 2-(Trimethylsilyl)ferrocenyl Imidazolylsulfonate

Abstract: Upon ortho lithiation ferrocenyl triflate and 1,1′-ferrocenediyl ditriflate undergo anionic thia-Fries rearrangements instead of triflate elimination. To differentiate between an ortho metalation and an ortho deprotonation, 2-(trimethylsilyl)ferrocenyl triflate was shown to undergo an anionic thia-Fries rearrangement to 2-((trifluoromethyl)sulfonyl)ferrocenol (5) in 84% yield upon treatment with tetrabutylammonium fluoride. Metalation of the respective tributylstannyl derivative with butyllithium also led to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Ferrocene is an aromatic organometallic compound, which easily undergoes electrophilic substitution. [26,27] Such an ortholithiation may give rise to rearrangement reactions, for example an anionic thia-Fries rearrangement [28,29] or a closely related anionic phospha-Fries rearrangement. [26,27] Such an ortholithiation may give rise to rearrangement reactions, for example an anionic thia-Fries rearrangement [28,29] or a closely related anionic phospha-Fries rearrangement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Ferrocene is an aromatic organometallic compound, which easily undergoes electrophilic substitution. [26,27] Such an ortholithiation may give rise to rearrangement reactions, for example an anionic thia-Fries rearrangement [28,29] or a closely related anionic phospha-Fries rearrangement. [26,27] Such an ortholithiation may give rise to rearrangement reactions, for example an anionic thia-Fries rearrangement [28,29] or a closely related anionic phospha-Fries rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Lithiation and 1,1′-dilithiation are well established, [25] and an ortho-lithiation in the presence of an ODG is also possible. [26,27] Such an ortholithiation may give rise to rearrangement reactions, for example an anionic thia-Fries rearrangement [28,29] or a closely related anionic phospha-Fries rearrangement. [30,31] We recently reported that the double anionic thia-Fries rearrangement at either one of the cyclopentadienyl ligands takes place in high yield under mild reaction conditions with an unprecedented interannular stereoinduction leading to the exclusive formation of the meso product.…”
Section: Introductionmentioning
confidence: 99%
“…and 1,2,1′,2′-tetradehydroferrocene ("ferrocenediyne") we recently reported the formation of 2-(trifluoromethylsulfonyl)ferrocenols by unprecedented anionic thia-Fries rearrangements of ferrocenyl triflates under mild reaction conditions in high yields instead of the desired elimination products. [34,35] An osmium complex with 1,2-dehydroferrocene as a ligand has been reported by Cullen et al as early as in 1992. [36] Herein, we report new or significantly improved syntheses of 1,2-dihaloferrocenes as well as ferrocenecarboxylic acid derivatives obtained by ortho-lithiation.…”
mentioning
confidence: 99%
“…Achiral 1,2,3,4,5-pentahalogenoferrocenes (Cl, Br, F) are accessible in a few steps, [15][16][17][18][19][20] while iterative metalation-functional group manipulation allows the tedious syntheses of pentasubstituted ferrocenes bearing up to three different substituents (Scheme 1). [21][22][23] Here, we report how the wise choice of substituents can enable hetero-1,2,3,4,5-pentasubstituted ferrocenes to be delivered, either as racemates or enantioenriched products, marking a milestone in metallocene science (Scheme 1).…”
mentioning
confidence: 99%